Nível de atividade física e capacidade funcional de pacientes com doença arterial periférica e fragilidade - Santos, Mayara Ferreira (2020)
Introduction: Patients with peripheral arterial disease (PAD) who present with intermittent claudication (IC) progress with functional decline and are allowed to perform activities of daily living. Among the outcomes that affect the elderly, a frailty syndrome has been a predictor for worsening physical capacity and inactivity in this population and is related to patients with PAD. Aim: To compare the level of physical activity and functional capacity of patients with peripheral arterial disease with and without frailty. Methods: This is an observational cross-sectional study, 232 patients with PAD and IC symptoms. A weakness was identified using the five criteria proposed by Fried, who considers the presence of three or more criteria for identifying the elderly person as an adult, one or two candidates as prehistoric and no criterion as robust. As several factors dependent on the levels of physical activity evaluated from the accelerometry, the ability to walk by the six-minute walk test, the perception of locomotion by the questionnaires Questionnaire of gait and battery of Tests Short Physical Performance Battery. Results: A robust patients were 6.5%, pre-frail patients were 72.0% and frail patients were 21.5%. Sedentary behavior and the level of physical activity were similar between the three groups. The total clause distance and the total walking distance were similar between the groups, the patients in the group with the lowest frequency of total walking with the groups (293 ± 86 m) vs pre-fragile group (331 ± 87) vs robust group (357 ± 74) p <0.021.The patients in the group under 50 years of age performed in longer time compared to other groups, in the usual 4-meter walk tests and without sitting and standing test. Patients in the pre-participant group also perform a longer time or sit test and stand up compared to the robust group. The patients in the group analyzed the lower values compared to the other groups for the total scores of the SPPB. Conclusion: There was a significant association between PAD and a frailty syndrome in relation to the requirements of frailty, functional capacity and sedentary behavior of patients with PAD with and without frailty